On multiple point coverage in wireless sensor networks - Shuhui Yang; Fei Dai; Cardei, M.; Jie Wu (IEEE International Conference on Mobile Adhoc and Sensor Systems Conference, 2005, 2005)
We consider a wireless sensor network consisting of a set of sensors deployed randomly. A point in the monitored area is covered if it is within the sensing range of a sensor. In some applications, when the network is sufficiently dense, area coverage can be approximated by guaranteeing point coverage. In this case, all the points of wireless devices could be used to represent the whole area, and the working sensors are supposed to cover all the sensors. Many applications related to security and reliability require guaranteed k-coverage of the area at all times. In this paper, we formalize the k-(connected) coverage set (k-CCSlk-CS) problems, develop a linear programming algorithm, and design two non-global solutions for them. Some theoretical analysis is also provided followed by simulation results